Diversitas Ektoparasit pada Ikan Bawal Bintang (Trachinotus blochii) Budi Daya di Teluk Lampung - Istikomah Istikomah; Agus Setiawan; Yudha Trinoegraha Adiputra; Supono Supono; Munti Sarida (Journal of Tropical Marine Science, 2023)
Snubnose pompano (Trachinotus blochii) mariculture commodity that admired in Lampung Bay due to faster growth and relatively struggle in dynamics environment changes likes floating cages. Disease infection become challenges when water quality degradation affects by tourism and mariculture activity in Lampung Bay. This research aimed to evaluate ectoparasite diversity that infect snubnose pompano and water qualities parameters at Lampung Bay. Survey conducted three times on 2022, September and October with snubnose pompano sampled amount 2.5% of population. Nine water quality variables were taken and measured in Seafarming Development Centre of Lampung. Results showed three species identified i.e. Pyragraphorus hollisae, Neobenedenia girellae and Benedenia sp. were infected snubnose pompano. Pyragraphorus hollisae dominated in intensity, prevalence while diversity index and uniformity index were low. Ammonia amount was high due to pollution and supported domination of Pyragraphorus hollisae. This research is expected to be one of the references in the treatment of ectoparasite infection in Snubnose pompano cultivation